The Effect of Pterygomasseteric Sling’s Area in the Postoperative Stability after Mandibular Setback Surgery. - Chen, Chun-Ming; Ting, Chun-Chan; Cheng, Jung-Hsuan; Hsu, Kun-Jung; Tseng, Yu-Chuan (BioMed Research International, 2017)
Purpose. The purpose of the present study was to investigate the correlation between the postoperative stability and area of pterygomasseteric sling (PMS). Materials and Methods. Forty patients of mandibular prognathism were treated by isolated mandibular setback. Serial lateral cephalograms were collected (preoperatively [T1], immediately after surgery [T2], and more than 1 year postoperatively [T3]). The postoperative stability (T32) was divided into 3 groups (total, forward, and backward movements). The areas of PMS, immediate surgical changes (T21), postoperative stability (T32), and final surgical change (T31) were analyzed by Student’s t-test, Pearson’s correlation coefficient, and multiple linear regression analysis. Results. The amount of mean setback (T21) was 12.6 mm in total group, 13.8 mm in forward group, and 10.8 mm in backward group. In the total group, postoperative stability (T32) was 0.6 mm forward and reduction area of PMS (T31) was 291 mm2 (17.2%). The reduction area of PMS (T31) was 298.2 mm2 (18%) and 263.1 (15.3%) mm2 in the forward group (3 mm) and backward group (2.4 mm), respectively. However, reduction area of PMS (T31) showed weak correlation with postoperative stability (T32) in all groups. Conclusion. Total and forward groups presented significant correlations between postoperative stability (T32) and amount of setback (T21).